1986
DOI: 10.1111/j.1944-9720.1986.tb03108.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies Used by Adolescents Studying French in New York Schools

Abstract: Studentsstudying French at Levels4 ZI, and ZIZ in a rural and urban school setting indicated on a questionnaire their use of learning strategies associated with classroom behaviors, individual study tactics, and social interactional behaviors. Successful learning behaviors related to communicative abilities, reading performance, and achievement on a standaniized test were found to vary due to the nature of the task. Years of languagestudy also influenced the use/ need of dvferent sets of strategies. Eight stmt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
5
16
1
Order By: Relevance
“…Similarly, Oxford and Nyikos (1989) found that years of study have a significant effect on the use of learning strategies. Ramirez (1986) reported similar results in his study of adolescent learners of French L2. He compared university students with high school students, Khalil (2005) found that university students used more strategies than high school students.…”
Section: H Duration Of English Studysupporting
confidence: 72%
“…Similarly, Oxford and Nyikos (1989) found that years of study have a significant effect on the use of learning strategies. Ramirez (1986) reported similar results in his study of adolescent learners of French L2. He compared university students with high school students, Khalil (2005) found that university students used more strategies than high school students.…”
Section: H Duration Of English Studysupporting
confidence: 72%
“…Ramirez, (1986) conducted a study on students in a small rural school taught by the same teacher. It was found that the communicative abilities of students in the rural school were lower than those in urban schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Questionnaire is used as one of the most widely data-elicitation tool (Goa, 2004). In addition, it is used by many researchers (Bialystok, 1981;Ehrman & Oxford, 1990;Oxford & Nyikos, 1989;Ramirez, 1986). High reliable questionnaires are preferred because we can be sure that, we will get the same result each time we measure the same thing.…”
Section: Self-report Questionnaires In the Studies Of Llssmentioning
confidence: 99%